Rhodium‐Catalyzed Synthesis of 4‐Bromo‐1, 2‐dihydroisoquinolines: Access to Bromonium Ylides by the Intramolecular Reaction of a Benzyl Bromide and an α‐Imino Carbene. Issue 14 (2nd March 2016) - He, Jun; Shi, Yinping; Cheng, Wanli; Man, Zengming; Yang, Dongdong; Li, Chuan‐Ying
Abstract: Highly functionalized 4‐bromo‐1, 2‐dihydroisoquinolines were synthesized from readily available 4‐(2‐(bromomethyl)phenyl)‐1‐sulfonyl‐1, 2, 3‐triazoles. A bromonium ylide is proposed as the key intermediate, which can be formed by the intramolecular nucleophilic attack of the benzyl bromide on the α‐imino rhodium carbene formed in the presence of the rhodium catalyst. Abstract : Illustrious ylides : 4‐Bromo‐1, 2‐dihydroisoquinolines were obtained conveniently from 4‐(2‐(bromomethyl)phenyl)‐1‐sulfonyl‐1, 2, 3‐triazoles1 through the formation of bromonium ylides from α‐imino rhodium carbene intermediates and subsequent rearrangement (see scheme). The versatile products participated as intermediates in a series of one‐pot reactions and were converted into valuable polycyclic systems.